Analisis Tindak Tutur Ekspresif Dalam Drama Burn The House Down - Rizki Maulana Sidiq; Rahmi Oktayory Wikarya (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
Expressive speech acts are actions performed to express the speaker’s psychological state. Research on expressive speech acts in literary works, particularly in drama, is essential to avoid misunderstandings in communication or interpreting utterances. This study aims to describe the function of expressive speech acts found in the drama Burn The House Down. The type of this research is qualitative with descriptive methods. The data in this study consists of utterances containing the expressive speech acts function in the drama Burn The House Down. The results of the study found 56 data divided into 9 functions of expressive speech acts, including: apologizing function 12 data, commending function 4 data, thanking function 15 data, anger function 5 data, blaming function 3 data, complaining function 5 data, criticizing function 7 data, welcoming 4 data, and deploring 1 data.